Intraoperative cardiac troponin T release and lactate metabolism during coronary artery surgery: comparison of beating heart with conventional coronary artery surgery with cardiopulmonary bypass. Issue 5 (1st May 1999) - Koh, T W; Carr-White, G S; DeSouza, A C; Ferdinand, F D; Hooper, J; Kemp, M; Gibson, D G; Pepper, J R
Abstract : OBJECTIVE: To compare cardiac troponin T release and lactate metabolism in coronary sinus and arterial blood during uncomplicated coronary grafting on the beating heart with conventional coronary grafting using cardiopulmonary bypass. DESIGN: A prospective observational study with simultaneous sampling of coronary sinus and arterial blood: before and 1, 4, 10, and 20 minutes after reperfusion for analysis of cardiac troponin T and lactate. Cardiac troponin T was also analysed in venous samples taken 3, 6, 24, 48, and 72 hours after surgery. SETTING: Cardiac surgical unit in a tertiary referral centre. PATIENTS: 18 patients undergoing coronary grafting on the beating heart (10 single vessel and eight two-vessel grafting) and eight undergoing two-vessel grafting with cardiopulmonary bypass. RESULTS: Cardiac troponin T was detected in coronary sinus blood in all patients by 20 minutes after beating heart coronary artery surgery before arterial concentrations were consistently increased. Peak arterial and coronary sinus cardiac troponin T values on the beating heart during single (0.03 (0 to 0.05) and 0.09 (0.07 to 0.16 μg/l, respectively) and two-vessel grafting (0.1 (0.07 to 0.11) and 0.19 (0.14 to 0.25) μg/l) were lower than the values obtained during cardiopulmonary bypass (0.64 (0.52 to 0.72) and 1.4 (0.9 to 2.0) μg/l) (p < 0.05). The area under the curve of venous cardiac troponin T over 72 hours for two-vessel grafting on the beating heart was less than with cardiopulmonary bypass (13 (10 to 16) v 68 (26 to 102) μg.h/l) (p < 0.001). Lactate extraction began within one minute of snare release during beating heart coronary surgery while lactate was still being produced 20 minutes after cross clamp release following cardiopulmonary bypass. CONCLUSIONS: Lower intraoperative and serial venous cardiac troponin T concentrations suggest a lesser degree of myocyte injury during beating heart coronary artery surgery than during cardiopulmonary bypass. Oxidative metabolism also recovers more rapidly with beating heart coronary artery surgery than with conventional coronary grafting. Coronary sinus cardiac troponin T concentrations increased earlier and were greater than arterial concentrations during beating heart surgery, suggesting that this may be a more sensitive method of intraoperative assessment of myocardial injury.